Perencanaan Information Technology Problem Management Berdasarkan ITIL V3 di Unit IS SSM Pada PT TELKOM - Perdana, Rhesa; Sudarmaningtyas, Pantjawati; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract: Telkom IS SSM (Service Support Management Information System) is a unit of PT Telekomunkasi Indonesian supporters for performing maintenance of telecommunication equipment infrastructure. IS SSM units do not have a standards regarding problem management process, making it less valid in determining the identification of a problem. Managers will cancel if the problem solver does not have a solution. As a result, the problem can not be resolved immediately disrupt the operations of the company. Due to the lack of specific parties to accept and perform filtering problem, the process of identifying the problem has not gone well. The solution of the above constraints make the Standard Operational Procedure (SOP) problem management process by following the ITIL V3 framework. Made through the four phases, the first to conduct stakeholder interviews to determine the processes that occur and the policy implemented. Second make the mapping process management problems. Third create a document that will generate SOPs, Work Instructions (IK), Records Work (RK), and the fourth stage of the planning document checks evaluate IT problem management with stakeholders in the IS unit SSM. The results of a study of IT problem management planning document it produces 12 Standard Operational Procedure (SOP), Work Instructions 22 (IK), and 61 Recording Work (RK), as well as recommendations to the IS SSM unit to form service desk and implement a written policy Keywords: IT Planning, Problem Management, Standart Operation Procedure (SOP)